Baseball and the media : how fans lose in today's coverage of the game - Castle, George (University of Nebraska Press, 2006)
What sports fans read, watch, and listen to at home often isn't the real story coming out of the locker room or the front office. George Castle should know; he's covered baseball in Chicago for decades and witnessed the widening gulf between the media and the teams they're supposed to cover--and the resulting widespread misinformation about the inner workings of the game. In this book, Castle chronicles from the inside the decline of baseball reporting and shows in clear and practical terms how ill-served today's sports followers are by those they trust for the straight story.